A universal cross-linking binding polymer composite for ultrahigh-loading Li-ion battery electrodes. Issue 19 (5th May 2020) - Wang, Dong; Zhang, Qian; Liu, Jie; Zhao, Erying; Li, Zhenwei; Yang, Yu; Guo, Ziyang; Wang, Lei; Zhang, Shanqing
Abstract : A general, facile-operability, and sustainable strategy to achieve ultrahigh-loading electrodes has been proposed that is simply replacing the traditional PVDF binder with an eco-friendly and robust c-PAA-XG binder with a high-efficiency damper. Abstract : To obtain high energy density, it is crucial to fabricate high-loading electrodes, which is severely hindered by their mechanical degeneration. Furthermore, a general strategy with low cost, eco-friendliness, and facile operability is urgently required for wide application. Herein, a novel 3D network binder with an efficient damper is proposed via thermal condensation of polyacrylic acid and xanthan gum (c-PAA-XG), in which the covalent crosslinking provides robust mechanical strength to withstand the mechanical degeneration. Meanwhile, due to abundant dynamic intermolecular hydrogen bonds and molecular chain weaving, the double-helix-structure XG can partly deform and self-assemble and act as a high-efficiency damper to protect the network binder from fracture when large impulse occurs under high loading. Consequently, a wide range of ultrahigh-loading electrodes can be successfully achieved through simply applying this c-PAA-XG binder with traditional doctor blade coating technology on planar current collector. In particular, for the nano/micro-Si/C anode with a high loading of 18.3 mg cm −2, an ultrahigh reversible areal capacity of 27.7 mA h cm −2 can be delivered. Reaction kinetics investigations suggest that the charge–discharge process of the Si/C electrode is dominated by a capacitive-controlled behavior, resulting in fast storage/release of Li + in high-loading electrodes. Furthermore, the c-PAA-XG binder has the advantages of low cost, eco-friendliness, and water-solubility, resulting in a sustainable electrode fabrication.